AESTHETICS OF THE LITERARY DIRECTION ROMANTICISM (Scientific journal of the Fergana State University, 2024)
The romanticism trend that appeared in the European literature in the 18th century influenced the literature of other countries, as well as the literature of Azerbaijan, and gave impetus to the creation of this trend. The main aspect that distinguished romanticism from other trends lwas the romantics' view of life. As a rule, the representatives of this trend did not write life and the truths of life as they saw them, but as they wanted to see them. Romantics were in search of ideal truth.  Therefore, they gave priority to spiritual values rather than material values. The main representatives of the Romanticism trend idealized human, nature, life, the past, in short, all of humanity, and went in search of truth.